Fostering technical entrepreneurship in research communities granting scholarships to would-be entrepreneurs - Reitan, Bjornar
Experiences from a public measure with the aim of fostering technical entrepreneurship are presented. The measure-a scholarship programme-is positioned at the preparation stage of a new business formation process, with the aim of achieving high quality preparation. The target groups are scientists and academics who want to establish a new venture in a high-tech field. The programme has not been as huge a success as expected. It is not appropriate according to the criteria of realism, complementarity and compatibility. Assessing the success of the established new technology-based firms (NTBFs), we find that in quantitative terms the programme has to be categorized as a success. The start-up rate is 89 percent, the survival rate 73.7 percent and the 'commercial utilization rate' 82.8 percent. However, in qualitative terms, the programme is not too successful. Most of the NTBFs do not contribute substantially to employment. Considering their turnover and net income before taxes, most of the firms are small and unprofitable. For the public fostering of technical entrepreneurship at universities and research institutions, the implications are that they have to attach great importance to creating an environment supportive of technical entrepreneurship. The role of the incubator is very important for both the short-run and long-run success of NTBFs. The university or research institution as an incubator can, when playing a proper role, reduce some problems NTBFs experience later and thus strengthen their qualitative performance.
To keep up its competitive position, Norway has felt that its industry should be focused more on knowledge based production. Scientists and academics are being encouraged to establish new ventures in high-tech fields by means of a scholarship programme. The paper assesses the strengths and weaknesses of the programme.
Keywords: Technical entrepreneurship